Reconstruction of Morphological (Ê»Ilmu Sharf) Learning Methods For Arabic Language and Literature Students/ Rekonstruksi Metode Pembelajaran Morfologi (`Ilmu Sharf) Bagi Mahasiswa Jurusan Bahasa Dan Sastra Arab - Muzakki, Akhmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Success in learning Arabic, both in reading skills (qirÄÊ»ah), listening (istimÄ`), speaking (kalÄm), writing (kitÄbah) and syntactic abilities (qawÄÊ»id), the role of mastery of morphology (Ê»ilm sharf) is very decisive. This study aims to find a new learning method that is fun, meaningful, and effective. This type of research is an experiment with the subject of research students of the 2nd semester of Arabic Language and Literature Department 2019/2020 Faculty of Humanities UIN Maulana Malik Ibrahim Malang, Indonesia. This study indicates that the hijÄÊ»iyah letter formula method makes students excited to learn morphology compared to conventional methods. The test results in the control class and the experimental class, two steps to conclude the independent sample t-test: first, looking at the Equal Variances Assumed, it is known that the Sig. (2-tailed) value is 0.000 Î± 0.05. Second, based on the comparison between the t-count value of 4.669 t-table of 2.021. From these two decisions, it can be concluded that H0 is rejected and Ha is accepted; namely, the letter hijÄÊ»iyah formula method has a significant effect on student learning outcomes in the morphology subject.